2002
DOI: 10.1080/089106002760002748
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationships between Bacteriological and Chemical Variations in Lake Pamvotis - Greece

Abstract: The relationships between indicator bacteria and the organic load were conducted over a year in Lake Pamvotis, in northwest Greece. Total coliforms (TC) and fecal coliforms (FC) were found in water samples from ve different sampling stations. Organic load was estimated using biological oxygen demand (BOD) and chemical oxygen demand (COD) parameters. Increased TC and FC levels were found close to heavily polluted areas. Near-bottom samples had higher levels of bacteria and the numbers of TC and FC were increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…Pearson et al [ 16 ] reported that, faecal coliforms died more rapidly when pH conditions were increased above 8.50, even in a nutrient rich condition, suggesting the influence of pH for the survival of faecal coliform in water systems. The concentration and distribution of faecal coliform also depends on tropical conditions [ 17 ] and indirectly on the physicochemical conditions of the water [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pearson et al [ 16 ] reported that, faecal coliforms died more rapidly when pH conditions were increased above 8.50, even in a nutrient rich condition, suggesting the influence of pH for the survival of faecal coliform in water systems. The concentration and distribution of faecal coliform also depends on tropical conditions [ 17 ] and indirectly on the physicochemical conditions of the water [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are controlled by varying factors in different aquatic environments. In surface water, faecal coliform survival and concentration is much affected by physical and climatic factors such as water temperature, rainfall, runoff, tidal conditions, solar radiation, dissolved nutrients, competition with other bacteria as well as other physicochemical conditions [ 17 19 , 28 , 29 ]. Geochemical processes like weathering, dissolution, hydrolysis, precipitation, adsorption, and ion exchange as well as oxidation reduction and biochemical reactions are major controlling factors for the chemistry of groundwater [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their disappearance rates from surface waters depend on a number of factors such as the availability of nutrients, temperature, salinity, turbidity, degree of water mixing, solar radiation, predation, and competition (Hood and Ness 1982;Flint 1987;Auer and Niehaus 1993). However, temperature and solar radiation are considered to be the most important abiotic factors (Esham and Sizemore 1998;Kagalou et al 2002;Xu et al 2002;Chigbu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…NAUMANN 1924, THIENEMANN 1925, PESTA 1929, RAWSON 1956, BRUNDIN 1958, στα μεσότροφα (NAUMANN 1921), στα εύτροφα και στα υπερεύτροφα οικοσυστήμα (π.χ. WEBER 1907, WEST AND WEST 1909, TEILING 1916, THIENEMANN 1925, MORTIMER 1941, 1942, MOUSTAKA-GOUNI AND TSEKOS 1989, MOUSTAKA-GOUNI 1993, KAGALOU ET AL. 2002.…”
Section: ταξινόμηση εσωτερικών υδάτωνunclassified